Nematicity and Glassy Behavior Probed by Nuclear Magnetic Resonance in Iron-Based Superconductors - Curro, N. J.; Kissikov, T.; Tanatar, M. A.; Prozorov, R.; Bud’ko, S. L.; Canfield, P. C. (Frontiers in Physics, 2022)
Nuclear magnetic resonance provides a wealth of information about the magnetic and nematic degrees of freedom in the iron-based superconductors. A striking observation is that the spin lattice relaxation rate is inhomogeneous with a standard deviation that correlates with the nematic susceptibility. Moreover, the spin lattice relaxation is strongly affected by uniaxial strain, and in doped samples it depends sensitively upon the history of the applied strain. These observations suggest that quenched strain fields associated with doping atoms induce a nematic glass in the iron pnictide materials.